Studying Generations Multidisciplinary Perspectives - Kingstone, Helen; Bristow, Jennie (Bristol University Press, 2024)
Available Open Access digitally under CC-BY-NC-ND licence. This collection introduces and explores the growing field of generational studies, providing a comprehensive overview of its strengths and limitations. With contributions from academics across a range of disciplines, the book showcases the concept's interdisciplinary potential by applying a generational lens to fields including sociology, literature, history, psychology, media studies and politics. Offering fresh perspectives, this original collection is a valuable addition to the field, opening new avenues for generational thinking.